Analisis Kinerja Unit Lost And Found Dalam Penanganan Bagasi Hilang Dan Rusak Maskapai Wings Air Di PT. Merpati Angkasa Abadi Bandar Udara Sultan Muhammad Kaharuddin III Sumbawa - Faril Aditya Pratama; Febriansyah Ignas Pradana (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study was made to determine the performance of Lost and Found unit in handling lost and damaged baggage, which aims to analyze the performance of Lost and Found unit in handling lost and damaged baggage at PT Merpati Angkasa Abadi Sultan Muhammad Kaharuddin III Sumbawa Airport. The research method uses a qualitative method, namely with the stages of observation, interviews, and documentation. It is known that the Lost and Found unit of Wings Airline at PT Merpati Angkasa Abadi Sultan Muhammad Kaharuddin III Sumbawa Airport is not in accordance with the SOP (Standard Operational Procedure), and there are several things that must be further improved by the Lost and Found unit in the future in carrying out its duties and taking full responsibility for passenger inconvenience about problems regarding luggage. It is expected to improve the form and quality of better performance for lost and found unit officers in handling Wings Air airline passenger baggage in order to minimize and avoid baggage irregularities and things that harm for passengers.